Immunoexpression pattern of TLR3 and TLR7 in minor salivary gland adenoid cystic carcinoma and its role in prognosis - Rytkönen, Aleksi (Elsevier, 2025)
Objectives: Adenoid cystic carcinoma (ACC) of the salivary glands has poor long-term prognosis and a high metastatic rate. Toll-like receptors (TLRs), first-line immune activators, have been associated with both tumor progression and suppression. We aimed to study TLR3 and TLR7 behavior in ACC.
Materials and methods: We studied TLR3 and TLR7 immunoexpression of 46 minor salivary gland ACCs diagnosed at the Department of Otorhinolaryngology - Head and Neck Surgery, Helsinki University Hospital, Helsinki, Finland over the period 1974-2012. The associations of TLR3 and TLR7 immunoexpression with clinicopathological factors were evaluated by χ2-test and Fisher's exact test.
Results: In the majority of samples, both TLR3 and TLR7 were immunoexpressed in cytoplasm. The immunoexpression was heterogeneous between individual tumors. Stronger TLR7 immunoexpression associated with recurrence rate and poorer disease-specific survival (DSS). TLR3 did not associate significantly with survival although we found an inverse correlation between TLR3 and TLR7 immunopositivity. Hence, when TLR3 immunoexpression was negative or mild, TLR7 immunoexpression was moderate to strong, and vice versa.
Conclusions: TLR3 and TLR7 are immunoexpressed in minor salivary gland ACC. TLR7 is potentially an independent prognostic marker for recurrence rate and DSS.